2019
DOI: 10.1038/s41568-019-0116-x
|View full text |Cite
|
Sign up to set email alerts
|

The evolving landscape of biomarkers for checkpoint inhibitor immunotherapy

Abstract: Checkpoint inhibitor-based immunotherapies that target cytotoxic T lymphocyte antigen 4 (CTLA4) or the programmed cell death 1 (PD1) pathway have achieved impressive success in the treatment of different cancer types. Yet, only a subset of patients derive clinical benefit. It is thus critical to understand the determinants driving response, resistance and adverse effects. In this Review, we discuss recent work demonstrating that immune checkpoint inhibitor efficacy is affected by a combination of factors invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
1,587
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,843 publications
(1,624 citation statements)
references
References 259 publications
(271 reference statements)
24
1,587
0
13
Order By: Relevance
“…In recent years, with the breakthroughs in the research of immunological checkpoint, the targeted inhibitors have been used in the field of cancer immunotherapy, showing unique effects. The humanized anti‐CTLA4 antibody ipilimumab was approved by the US Food and Drug Administration for clinical treatment of metastatic melanoma in 2011 . At the same time, PD‐1‐PD‐L1‐axis antibody has been approved for second‐line or first‐line therapy for the treatment of melanoma, lymphoma, lung cancer, renal cell carcinoma, head and neck squamous cell carcinoma, bladder cancer, liver cancer, and gastroesophageal cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, with the breakthroughs in the research of immunological checkpoint, the targeted inhibitors have been used in the field of cancer immunotherapy, showing unique effects. The humanized anti‐CTLA4 antibody ipilimumab was approved by the US Food and Drug Administration for clinical treatment of metastatic melanoma in 2011 . At the same time, PD‐1‐PD‐L1‐axis antibody has been approved for second‐line or first‐line therapy for the treatment of melanoma, lymphoma, lung cancer, renal cell carcinoma, head and neck squamous cell carcinoma, bladder cancer, liver cancer, and gastroesophageal cancer .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, PD‐1‐PD‐L1‐axis antibody has been approved for second‐line or first‐line therapy for the treatment of melanoma, lymphoma, lung cancer, renal cell carcinoma, head and neck squamous cell carcinoma, bladder cancer, liver cancer, and gastroesophageal cancer . However, most of the patients who receive immunological checkpoint block treatment did not benefit from it . Herbst et al conducted a large sample of clinical randomized controlled trials, pembrolizumab achieves extended OS and has a favorable benefit‐to‐risk profile in patients with PD‐L1 positive advanced non‐small‐cell lung cancer, and a phase II basket study (KEYNOTE‐158) investigated the antitumor activity and safety of pembrolizumab in multiple cancer types, concluded that in previously treated advanced cervical cancer: PD‐L1–positive tumors have a stronger response after pembrolizumab treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Readers who want to get additional details on this type of technology are referred to more technical reviews focusing on other application fields . Another area that urges for personalized approaches is immune oncology, which shows impressive survival advantages, but only for a fraction of all patients. Microfluidic solutions for prioritizing patients that would profit from those treatments have enormous potential and are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…This hurdle, known as checkpoint blockade, can be overcome by the release of proinflammatory cytokines (Noy & Pollard, ), such as TNF‐α, IFN‐γ which induces the activation of antitumoral macrophages, or mainly, by using antibodies blocking immune‐suppressor molecules present in activated CD8 + T cells such as PD‐1 and CTL‐4 (Havel, Chowell, & Chan, ; Ribas & Wolchok, ). Note that checkpoint inhibitor (CPI) blockade using antibodies, principally anti‐PD‐1, anti‐PD‐1 ligand (PD‐L1) and anti‐CTLA‐4, have been shown to be the most effective treatments in many different tumours including melanoma, non‐small cell lung cancer, kidney cancer, bladder cancer, head and neck cancers, Hodgkin lymphoma or Merkel cell carcinoma (Havel et al, ; Ribas & Wolchok, ). Most patients, however, (~75%) do not respond and there is usual appearance of tumours resistance to CPI treatments (Friedrich et al, ; Kim, Herbst, & Chen, ).…”
Section: Next Generation Of Immunotherapiesmentioning
confidence: 99%